Guideline on credit value and student learning time calculation for medical specialty programmes - Mohd Ismail, Aletza; Mohd Taib, Niazlin; Samsudin, Intan Nureslyna; Abdul Hamid, Nazifah; Harun, Azian; Abdullah, Maizaton Atmadini; Mohd Tohit, Eusni Rahayu; Md Fauzi, Suria Hayati; Ibrahim, Rosni; Mohamed, Normi Ngah; Ismail, Noor Akmal Shareela; Mohd Ali, Razana; et al. (Majlis Dekan Fakulti Perubatan Universiti Awam Malaysia (MDFPUAM), 2024)
The guideline aims to establish a consistent methodology for calculating credit hours across speciality programmes offered by universities, which are jointly coordinated by respective Specialty Committees (Jawatankuasa Kepakaran Perubatan). The revised version corrects some typing errors and removes statements that create confusion.